DMSO-enhanced N-isopropylacrylamide/sodium alginate hydrogel for saline soil desalination - Zhengyue Zhu; Jiancong Ye; Tao Ye; Jialong Zou; Junjie Ye; Qi Li; Yan Liu (Results in Chemistry)
The effects of different additions of dimethyl sulfoxide (DMSO) to poly(N-isopropyl acrylamide)/sodium alginate hydrogels(D-PNIPAM/SA) on the desalination of saline soil were investigated in this study. The effects of liquid absorption rate(LAR) of the D-PNIPAM/SA by temperature, NaCl concentration, and DMSO addition amount were studied. And the deswelling rate(DR) tests of different DMSO addition amounts were also investigated. The LAR decreased significantly with the temperature increase from 20 °C to 35 °C and with the increase of NaCl concentration from 0.597 g/L to 7.714 g/L. The LAR increased while the DR decreased with the DMSO addition increased from 0 ml to 3.5 ml. The results indicated that the optimal addition of the DMSO was 3.5 ml. In this addition, the D-PNIPAM/SA was observed in its best form by an Ultra-depth of field 3D microscope, and the phase transition temperature was reduced to −2.95 °C. In NaCl solution, DMSO was added from 0 ml to 3.5 ml, and the D-PNIPAM/SA absorption rate increased from 6.60 g/g to 12.41 g/g.In the desalination of saline soil study, the desalination rate of the D-PNIPAM/SA was reached 88.609 % in the saline soil solution test, and the desalination rate reached 94.765 % in the dry saline soil test.